2022
DOI: 10.3390/ijerph19159077
|View full text |Cite
|
Sign up to set email alerts
|

Play Badminton Forever: A Systematic Review of Health Benefits

Abstract: Regular physical activity (PA) engagement has multiple benefits for individual general health at all ages and life stages. The present work focuses on badminton, which is one of the most popular sports worldwide. The aim was to conduct a systematic review focused on examining and analysing this sport and the benefits it brings to the health of those who engage in it. Examination was conducted from the viewpoint of overall health and provides an overview of the current state-of-the-art as presented in published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…The participation of badminton in Indonesia is relatively high, and has a very good development [18]. Badminton also has a positive effect on physical health, particularly in improving heart and lung function, as well as on the development of basic physical capacities [19].…”
Section: Discussionmentioning
confidence: 99%
“…The participation of badminton in Indonesia is relatively high, and has a very good development [18]. Badminton also has a positive effect on physical health, particularly in improving heart and lung function, as well as on the development of basic physical capacities [19].…”
Section: Discussionmentioning
confidence: 99%
“…Badminton is a globally popular sport with recognized physical and mental health benefits [1]. However, physical disabilities often hinder individuals from engaging in this activity.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are 12 modifiable risk factors to prevent and intervene with dementia, such as physical inactivity, obesity, depression, social isolation, diabetes, hypertension, head injury, smoking, air pollution, alcohol, hearing loss, and low educational level [8], previous studies reported the benefits of badminton in intervening for physical, social, and psychological health [9][10][11][12]. Considering physical health, several studies and reviews demonstrated the effect of badminton on cardiac and respiratory function, including increasing maximal oxygen uptake (VO2max) and decreasing asthma, optic function, body shape, increasing bone mineral density, lower risk of coronary heart disease, and physical abilities (e.g., speed, flexibility, endurance, strength, vertical jump, muscle coordination, manipulation, and motor skills).…”
Section: Introductionmentioning
confidence: 99%
“…Considering physical health, several studies and reviews demonstrated the effect of badminton on cardiac and respiratory function, including increasing maximal oxygen uptake (VO2max) and decreasing asthma, optic function, body shape, increasing bone mineral density, lower risk of coronary heart disease, and physical abilities (e.g., speed, flexibility, endurance, strength, vertical jump, muscle coordination, manipulation, and motor skills). Considering social health, badminton has a good impact on social relationships, personal development, mood regulation, and intrinsic motivation, following increasing fun and social engagement motives, besides psychological benefits on improving cognitive function, alertness, concentration, attention, depressive symptoms, and general motivation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%